Integrative Approaches to Enhancing Performance and Collaboration among Medical Clinic Staff: A Critical Analysis - Alyami, Hassan Yousef Mushabbab Alateeq; Alyami, Naqtan Ali; Alyami, Hussain bin Yousef bin Mushabbab; Alyami , Thoraya Saad Saeed; Almakrami, Mohsen Mohammed A; Al Hammam , Salim Yahya M; Almakrami, Mohammed Mohsen Ali; Alhammam, Salem Yahia; al sawidan, Mohammed saleh fahud; Alshiban, Fahad Ali (Journal of Ecohumanism, 2024)
This article critically examines integrative approaches aimed at enhancing performance and collaboration among medical clinic staff, including physicians, nurses, administrative personnel, laboratory technicians, and pharmacists. With the increasing complexity of healthcare delivery, the need for interdisciplinary teamwork has become paramount. The analysis explores evidence-based strategies such as team-based training programs, collaborative technologies, and leadership-driven initiatives to address common challenges like communication gaps, role ambiguity, and resistance to change. Findings indicate that these approaches significantly improve staff performance, reduce medical errors, and enhance patient satisfaction. The discussion highlights the role of effective leadership, organizational culture, and tailored interventions in fostering a cohesive team environment. The article concludes with actionable recommendations for clinic managers, policymakers, and researchers to further optimize collaboration and performance in medical clinics.